Interactive E-Module Development through Chemistry Magazine on Kvisoft Flipbook Maker Application for Chemistry Learning in Second Semester at Second Grade Senior High School - Roza Linda; H Herdini; Ika Sulistya S; Teja Pratama Putra (Journal of Science Learning, 2018)
This research is an innovative development on teaching materials in order to intensify the movement of "Satu Guru Satu Buku (SAGUSABU)" and to prepare skillful media users on mastering Information and Communication Technologies (ICT). The resulting prototype is an interactive e-module named Chemistry Magazine which have two editions: ionic equilibrium and pH of buffer solution and solubility equilibrium. Applying research and development study design with Plomp model, assessment and suggestion by validator team on material substance aspect, instructional design, display (visual communication) and software utilization using validation sheet are in valid category. Percentage of legality score by media validator is 91.70% for ionic equilibrium and pH of buffer solution edition; and 94.18% for solubility equilibrium edition, whereas by material validator is 93.75% and 94.45% on each. Users response score rate through questionnaire for teachers and students on ionic equilibrium edition and pH of buffer solution edition are 87.08% and 88.45%; meanwhile 94,25% and 91,43%  are obtained from solubility equilibrium edition.